TECHNOLOGICAL CONTEXT AND ORGANISATIONAL CONTEXT CROSS-BORDER E-COMMERCE SMEs’ PERFORMANCE IN HEBEI - Zhang Jingjing; Sidah Idris (International Journal of Accounting, Finance and Business, 2024)
China's cross-border e-commerce (CBEC) transactions have increased significantly in recent years. In 2013, the overall amount of the country's CBEC transactions was 3.1 trillion Chinese yuan, growing to 15.7 trillion in 2022 with an average high year-on-year growth rate. However, overall growth remains declining. This study aims to investigate the demand for information technology in international trade as it has spawned the growth of CBEC. This study will focus on the technological and organizational contexts and their effects on SMEs' performance in Hebei Province. It is the embodiment of a new economic form, paving the way for a new path of development by combining the Internet with traditional industries. This study will explore the determinants of CBEC SMEs' performance in Hebei Province. This study adopts a systematic literature review on CBEC SMEs in China, which still remains limited. This study plays a significant role in industry innovations that have been emerging by focusing on new industries, new models, and new engines for foreign trade.